Reconfigurable soft body trajectories using unidirectionally stretchable composite laminae - Sang Yup Kim (Nature Portfolio, 2019)
Soft actuators are typically confined to a single, predetermined deformation trajectory. Here, the authors report on a bioinspired self-adhesive material which can be attached, detached, and re-attached to expanding soft bodies to render reconfigurable and controllable deformation trajectories.